Test of Host Sanction Hypothesis in Soybean Plants Co-inoculated with Nitrogen Fixing and Non-fixing Bradyrhizobium japonicum - Marco, Diana Elizabeth (2015)
Aims: We tested the proposed mechanism for potential sanctions, that the plant would reduce viability of non-fixing rhizobia inside nodules, performing viable Bradyrhizobium japonicum counts from co-occupied and single-occupied nodules in co-inoculated soybean plants. Study Design: Plants were co-inoculated with two strains of B. japonicum, a highly efficient nitrogen fixing wild-type strain BJD321, and the non-fixing, nifH mutant derivative A3, to produce co-occupied nodules as well as single-occupied nodules. Strain A3 lacks nitrogenase activity but shows similar infection and nodule formation levels respect to the wild-type. As the strains used are equivalent in competitive and nodulation abilities and only differ in the nitrogen fixation ability (by nitrogenase inactivation), and share the same plant, root and even nodule, we can assert that themechanism being tested is plant host sanction, and no other proposed mechanisms like partner choice. Place and Duration of Study: Nitrogen Metabolism Lab, Department of Soil Microbiology and Symbiotic Systems at Zaidín Experimental Station (CSIC State Agency, Granada, Spain). 2010- 2011. Methodology: Axenic seedlings of soybean (Glycine max) cultivar Williams were inoculated with 2 ml of bacterial suspension of BJD321 or A3 strains, alone or in 1:1 mixture and supplied with sterilized N free nutrient solution. Four weeks after inoculation plants of each inoculation treatment (BJD321 + A3, BJD321 only, A3 only) were harvested, nodules were counted and weighed and plated to determine rhizobial strain occupation and population. In the aerial part of plants, determinations of weight, N and C content were done. Results: Co-inoculated plants and plants only inoculated with the BJD321 strain showed a similar nitrogen fixation since they did not differ in dry weight, total N content and total C content. Plants with different inoculation treatments (BJD321 + A3, BJD321 only and A3 only) did not differ in nodule number. In co-inoculated plants, nodule occupation did not differ from the expected among strains (about 33% BJD321 + A3, BJD321 only and A3 only), and the weight of nodules occupied by both strains, BJD321 or A3 alone did not differ. In co-inoculated plants rhizobial viability did not differ between BJD321 and A3 strains, either comparing co-occupied nodules or single-occupied nodules. Nodule size and CFU of rhizobia inside nodules were not correlated, either in coinoculated plants or plants inoculated with BJD321 strain alone. Conclusion: We can conclude that in the soybean-B. japonicum system, plants facing the presence of fixing and non-fixing rhizobial strains do not sanction cheating and can perform as well as plants inoculated with the fixing strain alone.